2012
DOI: 10.1074/jbc.m112.349126
|View full text |Cite
|
Sign up to set email alerts
|

Live Imaging Reveals Differing Roles of Macrophages and Neutrophils during Zebrafish Tail Fin Regeneration

Abstract: Background: Macrophages and neutrophils are key phagocytes in regeneration. Results: Neutrophils are the primary phagocytes in the inflammatory stage and are dispensable for zebrafish fin regeneration, whereas macrophages mainly function in the resolution stage and are required for fin regeneration. Conclusion: Macrophages and neutrophils behave differently during zebrafish fin injury and regeneration. Significance: Our study documents that macrophages and neutrophils play distinct functions in tissue regenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
264
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(285 citation statements)
references
References 47 publications
19
264
2
Order By: Relevance
“…Under this scab, the granulation tissue started to spread and macrophages appeared to remove large cell debris as well as apoptotic neutrophils. These macrophages are the key scavengers for resolving inflammation and facilitating tissue regeneration (Li et al, 2012). An accentuated inflammatory rim seemed more obvious around the untreated burns than in the treated ones.…”
Section: Discussionmentioning
confidence: 99%
“…Under this scab, the granulation tissue started to spread and macrophages appeared to remove large cell debris as well as apoptotic neutrophils. These macrophages are the key scavengers for resolving inflammation and facilitating tissue regeneration (Li et al, 2012). An accentuated inflammatory rim seemed more obvious around the untreated burns than in the treated ones.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, endogenous zDusp6 underwent degradation in zebrafish embryos after H 2 O 2 treatment ( Figure 5C and 5D) signal is required for the rapid inflammatory response in the tail-fin epithelium of zebrafish larvae [25,26]. To differentiate potentially dual function of H 2 O 2 in recruiting inflammatory cells and priming heart regeneration, we examined temporal and spatial distribution of immune cells during heart regeneration by labeling macrophages and neutrophils with either anti-lymphocyte cytosolic protein 1 (Lcp1) or Tg(coro1a:EGFP) [41]. We found that Lcp1 + leukocytes appeared around 3 dpa, peaked at 7 and 14 dpa, decreased at 19 dpa and almost disappeared at 24 dpa ( Figure 6A-6F), and the recruitment occurred in a H 2 O 2 -dependent manner ( Figure 6G and 6I).…”
Section: The Duox-h 2 O 2 -Dusp6 Pathway Primes Myocardial Regeneratimentioning
confidence: 99%
“…Tg(tcf21:nucEGFP) was previously reported [30]. Tg(coro1a:EGFP) was provided by Dr Zilong Wen [41], Tg(dusp6:EGFP) transgenic zebrafish were obtained from Dr Michael Tsang [40] and Tg(gata4:EGFP) transgenic zebrafish were kindly provided by Dr Todd Evans [51]. The zebrafish myl7 promoter was provided by Dr C Geoff Burns [52]; pHyPer-Cyto cDNA clone was purchased from Evrogen (Cat No.…”
Section: Zebrafish Linesmentioning
confidence: 99%
“…Delayed regeneration of tail fin after macrophage depletion Zebrafish embryo [20] Macrophages are required for limb regeneration Adult salamander [22] Macrophages phagocytize wound debris and induce fibroblast proliferation during skin repair…”
Section: Macrophage Plasticity and Polarizationmentioning
confidence: 99%